2001
DOI: 10.1302/0301-620x.83b2.0830289
|View full text |Cite
|
Sign up to set email alerts
|

Repair of cartilage defect in the rabbit with cultured mesenchymal stem cells from bone marrow

Abstract: In 16 mature New Zealand white rabbits mesenchymal stem cells were aspirated from the bone marrow, cultured in monolayer and implanted on to a full-thickness osteochondral defect artificially made on the patellar groove of the same rabbit. A further 13 rabbits served as a control group. The rabbits were killed after 14 weeks. Healing of the defect was investigated histologically using haematoxylin and eosin and Safranin-O staining and with immunohistochemical staining for type-II collagen. We also used a rever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
57
1
3

Year Published

2003
2003
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(66 citation statements)
references
References 0 publications
2
57
1
3
Order By: Relevance
“…Previous studies found that grafting of BMSCs could repair defects of the articular cartilage of rabbits by differentiating into chondrocytes and forming cartilaginous tissues [20,21]. Zhang's group successfully regenerated humanear-shaped cartilage by co-grafting human microtia chondrocytes with goat BMSCs in nude mice [4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies found that grafting of BMSCs could repair defects of the articular cartilage of rabbits by differentiating into chondrocytes and forming cartilaginous tissues [20,21]. Zhang's group successfully regenerated humanear-shaped cartilage by co-grafting human microtia chondrocytes with goat BMSCs in nude mice [4].…”
Section: Discussionmentioning
confidence: 99%
“…These results indicate that co-culture with chondrocytes could properly promote the chondrogenic differentiation of BMSCs, which may serve as a promising strategy for cartilage reconstruction. However, due to the limited sources of human BMSCs, animal BMSCs were dominantly employed for studies of chondrogenesis [4,20,21]. Albeit the drawing of bone marrow brings extra pain for patients, the application of BMSCs for regenerative medicine is not widely restricted.…”
Section: Discussionmentioning
confidence: 99%
“…in rabbit [13], goat [14], dog [15] and rat [16,17]. Recent works have also assessed the efficacy of different scaffolds containing embedded chondrocytes or multipotent stem cells to fill osteochondral defects [18][19][20]. In tissue engineering, several factors must be taken into account: (1) localization, depth and diameter of the chondral lesion, (2) the animal species considered, (3) the kind of scaffold and cells implanted, and (4) the programming of load impact after implantation.…”
Section: Discussionmentioning
confidence: 99%
“…Über verschiedene Evidenzwege lässt sich zeigen, das Östradiol mit der Synthese und Sekretion von Wachstumsfaktoren interagieren kann, darunter vor allem mit TGF("transforming growth factor")-β und IGF("insulin-like growth factor")-1. TGF-β reguliert die Chondrozytenproliferation und -differenzierung und kann sogar die Differenzierung von mesenchymalen Stammzellen in Chondrozyten stimulieren [24]. Die TGF-β-Expression wird dosisabhängig und biphasisch von Östradiol beeinflusst: Die Expression erhöht sich bei niedrigen (0,1 nmol/l) und verringert sich bei supraphysiologischen (10 nmol/l) Östradiol-konzentrationen [34].…”
Section: Effekte Von öStrogenen Auf Knorpelgewebeunclassified